2020
DOI: 10.1029/2020ja028396
|View full text |Cite
|
Sign up to set email alerts
|

ULF Wave Activity Observed in the Nighttime Ionosphere Above and Some Hours Before Strong Earthquakes

Abstract: We examine the relationship between earthquakes and ultralow frequency (ULF) wave activity in the nighttime ionosphere based on the electric field data in the direct current/ULF range observed by the DEMETER satellite over a~5.5 year period from May 2005 to November 2010. ULF wave activity is identified by an automatic detection algorithm and those which occur on the geomagnetic disturbed days (Kp > 3 at any time intervals) are discarded. Only the earthquakes with depth ≤70 km and occurring in the region of |M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…The distance between the center of each cell and epicenter was calculated to analyze the relationship of the distance from the epicenter, seismic magnitude, and occurrence time of the anomalies based on the statistical study. Meanwhile, similar to studies by Parrot (2012) and Ouyang et al (2020), a random dataset with 206 Mw ≥ 6.0 earthquakes was obtained to carry out comparative analysis with real earthquakes. De Santis et al ( 2019) compared their real results between real earthquakes and random anomalies.…”
Section: A Worldwide Analysis: Statistical Studymentioning
confidence: 99%
“…The distance between the center of each cell and epicenter was calculated to analyze the relationship of the distance from the epicenter, seismic magnitude, and occurrence time of the anomalies based on the statistical study. Meanwhile, similar to studies by Parrot (2012) and Ouyang et al (2020), a random dataset with 206 Mw ≥ 6.0 earthquakes was obtained to carry out comparative analysis with real earthquakes. De Santis et al ( 2019) compared their real results between real earthquakes and random anomalies.…”
Section: A Worldwide Analysis: Statistical Studymentioning
confidence: 99%
“…Additionally, the possibility of ground electromagnetic signals being propelled into atmosphere and ionosphere has been verified by satellite electromagnetic observations [14,15]. Many scholars have discovered abnormal changes in the electric and magnetic fields within the ULF range before earthquakes based on the observation data of DEMETER and other satellites [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…A few case studies have demonstrated anomalous electromagnetic signals in the ULF range before earthquakes observed by satellites, e.g., [10][11][12][13]. The most recent statistical study confirmed the association between earthquakes and ULF wave activity in the nighttime ionosphere [14]. It is common in pre-earthquake effect studies to use geomagnetic activity indices to exclude disturbances in the space environment.…”
Section: Introductionmentioning
confidence: 99%
“…However, electromagnetic disturbances in the ionosphere are affected by many energy sources other than intense geomagnetic activity. In addition, most previous studies on ULF disturbances related to earthquakes are based on the electric field in the DC/ULF band recorded by the DEMETER satellite [10][11][12]14,15]. However, only using electric field data limits further analyses of wave properties such as wave mode and polarization parameters.…”
Section: Introductionmentioning
confidence: 99%